Kesalahan Siswa dalam Mengerjakan Soal Matematika Ditinjau dari Gender - Zuhrotunnisa Zuhrotunnisa; Rina Puji Astuti; Widya Oetami (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2019)
The research aims to describe the student’s mistakes in doing mathematics problem observed on kind of gender. The data is taken based on the last odd semester evaluation academic year 2017/ 2018. Based on this data, gets the result as follows: 1) The male student’s can not draw the pattern yet, can not count the area yet, don’t know the formula of the equation of the line and low at the ability of counting. 2) The female student’s can draw the pattern, can not determine the area, and low in understanding the concept of looking for the ability of counting.